Acute effects of different warm-up protocols on anaerobic performance in teenage athletes - Faigenbaum, A.; Kang, J.; McFarland, J.; Bloom, J. M.; Magnatta, J.; Ratamess, N. A.; Hoffman, J. (Pediatric Exercise Science, 2006)
Although pre-event static stretching (SS) is an accepted practice in most youth programs, pre-event dynamic exercise (DY) is becoming popular. The purpose of this study was to examine the acute effects of pre-event SS, DY, and combined SS and DY (SDY) on vertical jump (VJ), medicine-ball toss (MB), 10-yard sprint (SP), and pro-agility shuttle run (AG) in teenage athletes (15.5 ± 0.9 years). Thirty athletes participated in three testing sessions in random order on three nonconsecutive days. Before testing, participants performed 5 min of walking/jogging followed by one of the following 10 min warm-up protocols: a) five static stretches (2 × 30 s), b) nine moderate-to-high-intensity dynamic movements (2 × 10 yards), or c) five static stretches (1 × 30 s) followed by the same nine dynamic movements (1 × 10 yards). Statistical analysis of the data revealed that performance on the VJ, MB, and SP were significantly (p < .05) improved after DY and SDY as compared with SS. There were no significant differences in AG after the 3 warm-up treatments. The results of this study indicate that pre-event dynamic exercise or static stretching followed by dynamic exercise might be more beneficial than pre-event static stretching alone in teenage athletes who perform power activities.